Black phosphorus mode-locked sub-100 fs bulk laser based on heterostructured Yb composite crystal. (1st December 2017) - Lou, Fei; Zhang, Baitao; Sun, Shijia; Hu, Chen; Lin, Zhoubin; Jiang, Jieyu; Zhang, Shuaiyi; Wang, Xia; Teng, Bing; He, Jingliang
Abstract: A physically combined heterostructured (PCH) Yb:KGW/Yb:SYB crystal is used to demonstrate a black phosphorus (BP) mode-locked sub-100 fs bulk laser. Near-transform-limited 75 fs pulses are yielded at 1054.6 nm with an output power of 1.03 W, corresponding to an optical-to-optical efficiency of 10%. This is the first implementation of the PCH concept into a mode-locked Yb-crystal laser to the best of our knowledge. The results not only illustrate the potential of the PCH Yb-crystal as an ideal candidate for realizing ultrafast lasers, but also indicate that BP mode-locking is a very promising approach for generating sub-100 fs pulses from a laser oscillator.